THE MODELLING OF CARGO TRANSSHIPMENT OPERATIONS USING THE BUSINESS PROCESS MODELLING TOOLS - Catalin POPA; Ionela GOIA (Scientific Journal of Silesian University of Technology. Series Transport)
This paperwork explores the transshipment operations at the Port of Constanta, Romania, focusing on the unloading of big bags from barges. Utilizing Business Process Management (BPM) software, the study models the transshipment process to identify optimization opportunities. The investigation reveals challenges such as coordination complexities and potential cargo damage, alongside the benefits of cost-efficiency and flexibility offered by transshipment services. Through literature review and analysis, the study emphasizes the importance of efficient business processes and the role of BPM software in enhancing operational efficiency. By employing Aura Portal Modeller for simulation, the study identifies bottlenecks and proposes optimization strategies for the transshipment process. The proposed measures include real-time cargo assessment, inventory tracking systems, equipment analysis, and storage layout optimization. This research contributes to the understanding of transshipment operations and highlights the effectiveness of BPM software in process visualization and analysis, offering insights for enhancing efficiency and mitigating delays in supply chain management.